Hero rising. Book 4, Darkmouth - Hegarty, Shane (Harper Collins London, 2017)
The edge-of-your-seat, monstrously-exciting, laugh-out-loud adventures of the most unfortunate monster-hunter ever to don armour$1! = (Bcontinue.s